Association between chronic pain and cognitive frailty among middle-aged and elderly individuals: evidence from the China Health and Retirement Longitudinal Study - Li, Tianjiao; Li, Lingxuan; Xie, Hongyang; Ping, Rongyu; Guo, Yane; Li, Dongmei; Zhang, Yuwei; Bai, Xiujuan; Sun, Bo (Frontiers in Aging Neuroscience, 2024)
BackgroundFrailty, particularly cognitive frailty, is an escalating public health issue. Cognitive frailty is defined by the simultaneous presence of physical frailty and cognitive impairment, without a confirmed diagnosis of dementia, and has become a significant geriatric syndrome. This study aimed to explore the association between chronic pain and the risk of cognitive frailty.MethodsWe utilized data from two waves (2011 and 2015) of the China Health and Retirement Longitudinal Study (CHARLS), conducting both cross-sectional and longitudinal analyses involving 17,705 Chinese adults aged 45 years and older. Chronic pain was defined as pain reported at both time points. Cognitive function was evaluated using a questionnaire adapted from the Telephone Interview for Cognitive Status. The frailty index (FI) was derived from a 30-item assessment. Cognitive frailty was characterized by the co-occurrence of cognitive impairment and physical frailty.ResultsAmong the 14,285 participants, 5.39% exhibited cognitive frailty at baseline. Both cross-sectional and longitudinal analyses indicated that individuals suffering from chronic pain faced a higher likelihood of developing cognitive frailty compared to those without pain. After adjusting for potential confounders, multivariate models also indicated a higher odds of cognitive frailty for participants with chronic pain.ConclusionChronic pain is significantly associated with an elevated risk of cognitive frailty among middle-aged and elderly individuals. These findings highlight the importance of managing chronic pain to mitigate the risk of cognitive frailty, thereby potentially enhancing the quality of life for the aging population and alleviating the economic burden on families and society.